2019
DOI: 10.1080/2000656x.2019.1693392
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of corrective osteotomy for malunited fractures of the distal radius

Abstract: The aim was to investigate the long-term outcome after corrective osteotomy for malunion of distal radius fractures. Radiological findings, function, activity performance, pain, health-related quality of life and self-efficacy were studied. Evaluation of 37 patients 3-10 years after osteotomy fixated with a volar plate. Conventional radiographs were taken. Grip strength and range of motion were evaluated. Scores from the Patient Rated Wrist Evaluation (PRWE) were compared with normative values. The RAND-36 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…The observed PROMs reported in our study are consistent with previous data reporting on the outcome of USO [12,14,15,17]. Moreover, these PROMs are comparable with those published following DRO, including PRWE (11 in our cohort vs. 12 to 22 in DRO [6,24,25]), QuickDASH (6.8 in our cohort vs. 10 to 16 in DRO [6,25,26], EQ-5D-5L (0.88 in our cohort vs. 0.84 in DRO [6]), satisfaction rate (84% in our cohort vs. 83% in DRO [6]), and NPS (73 in our cohort vs. 69 in DRO [6]. However, in the absence of preoperative data we are unable to comment on the degree of preoperative disability in patients whose predominant symptoms are due to ulnar positive variance.…”
Section: Discussionsupporting
confidence: 92%
“…The observed PROMs reported in our study are consistent with previous data reporting on the outcome of USO [12,14,15,17]. Moreover, these PROMs are comparable with those published following DRO, including PRWE (11 in our cohort vs. 12 to 22 in DRO [6,24,25]), QuickDASH (6.8 in our cohort vs. 10 to 16 in DRO [6,25,26], EQ-5D-5L (0.88 in our cohort vs. 0.84 in DRO [6]), satisfaction rate (84% in our cohort vs. 83% in DRO [6]), and NPS (73 in our cohort vs. 69 in DRO [6]. However, in the absence of preoperative data we are unable to comment on the degree of preoperative disability in patients whose predominant symptoms are due to ulnar positive variance.…”
Section: Discussionsupporting
confidence: 92%
“…All patients experienced some degree of pain after the surgery. They suggested corrective osteotomy for patients with a poor functional outcome after a distal radius fracture [13]. According to the patients' report, none of the patients had experienced pain until the last follow-up.…”
Section: Andreasson Et Al Reported the Outcome Of Correctivementioning
confidence: 99%
“…Ingrid Andreasson et al . reported good long‐term follow‐up outcomes for 37 patients with malunited fractures of distal radius who underwent corrective osteotomy using a volar plate 10 . Similarly, Kunihiro et al .…”
Section: Introductionmentioning
confidence: 99%
“…An increasing body of evidence suggests that corrective osteotomy with volar fixation is an effective method for treating distal radius fracture malunion due to its unique advantages, accounting for its increasing use by orthopaedists 2,8,9 . Ingrid Andreasson et al reported good long-term follow-up outcomes for 37 patients with malunited fractures of distal radius who underwent corrective osteotomy using a volar plate 10 . Similarly, Kunihiro et al reported that volar fixation had lower surgical technical requirements and fewer complications than dorsal fixation 11 .…”
Section: Introductionmentioning
confidence: 99%